Fenomena Cyberbullying pada Remaja - Rifauddin, Machsun (Khizanah al-Hikmah : Jurnal Ilmu Perpustakaan, Informasi, dan Kearsipan, 2016)
The advent of information technology, internet and social media are able to change the behavior of human beings in socializing and communicating. Communication without control in social media cause in advent a variety of crimes for example cyberbullying. Teenagers are accounted for the highest percentage as perpetrators or victims of cyberbullying on social media especially facebook. This article describes the phenomenon of cyberbullying in adolescence in social media facebook with some cases that occur in Indonesia. This article also describes the impact of cyberbullying for teens and solutions of cyberbullying and introduce ethics in using social media